Anais Estendidos Do IX Simpósio Brasileiro De Engenharia De Sistemas Computacionais (SBESC Estendido 2019) 2019
DOI: 10.5753/sbesc_estendido.2019.8641
|View full text |Cite
|
Sign up to set email alerts
|

Certificação Digital como Ferramenta de Segurança para Medidores Inteligentes

Abstract: In this paper, we present a digital certificate-based solution for smart meters. Our propose meets the identification requirements found in several scenarios related to Legal Metrology. Also, it extends previous models of smart meters authentication. This proposal results in a new class of digital certificate called "Metrologic Objects Digital Certificate." The ICP-Brasil Management Committee recently approved the use of these certificates. Fuel dispensers are the first implementation case. The objective is to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The understanding of the advantages and drawbacks of a CA-based PKI model is the first step to conceive of a blockchain-based PKI model. The CA-based PKI model described here comes from the work of Melo et al [ 5 ]. The authors presented an ongoing project proposing an architecture to implement digital certificates in fuel dispensers.…”
Section: Case Study: a Blockchain-based Pki For Smart Metersmentioning
confidence: 99%
See 3 more Smart Citations
“…The understanding of the advantages and drawbacks of a CA-based PKI model is the first step to conceive of a blockchain-based PKI model. The CA-based PKI model described here comes from the work of Melo et al [ 5 ]. The authors presented an ongoing project proposing an architecture to implement digital certificates in fuel dispensers.…”
Section: Case Study: a Blockchain-based Pki For Smart Metersmentioning
confidence: 99%
“…Rodrigues Filho et al [ 35 ] reported that, in Brazil, frauds related to fuel dispensers result in economic losses in the order of USD 300 million per year for all society. These reasons motivated the Brazilian National Institute of Metrology, Quality, and Technology (Inmetro ( (accessed on 30 December 2020))) to regulate and enforce the insertion of digital certificates into fuel dispensers [ 5 ].…”
Section: Case Study: a Blockchain-based Pki For Smart Metersmentioning
confidence: 99%
See 2 more Smart Citations